(untitled) (Eurasian Research Bulletin, 2024)
In the article, the scientific-theoretical views on the financing of physical education and sports are mentioned. In addition, the data on extra-budgetary incomes of sports institutions of the Republic of Karakalpakstan, regions and the city of Tashkent were analyzed. Proposals and recommendations for financing the field of physical education and sports have been developed